Information: XXIV International Scientific Conference “System Dynamice Society”, 30-31.07.06. Dynamical Monitoring in Creating informative Basis for Permanent Development - Michnowski, Lesław (Problemy Ekorozwoju, 2007)
The System Dynamic Society is an association around the famous Massachusetts Institute of Technology, which aims to support politics with systemic knowledge. SDS develops methods of system analysis and computer simulation of real – comprehensively recognizable – needs, conditions and policy consequences. These methods make it possible to create warning forecasts.